Corporate social responsibility and strategic market positioning for organizational success - Brown, Carlton, 1986-; Nwagbara, Uzoechi (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2019)
"This book explores the intricate relationship between marketing, organizational strategy and social responsibility, with a focus on ethical business and CSR-oriented marketing as a driver for sales peak performance. The book focuses on the commercial sector, which relies appreciably on ethical marketing/business to enhance sales peak performance and becomes successful in the long-run"--